Serine-Rich Repeat Adhesins Contribute to Streptococcus gordonii-Induced Maturation of Human Dendritic Cells - Ko, Eun Byeol; Kim, Sun Kyung; Seo, Ho Seong; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2017)
Dendritic cells (DCs) play a pivotal role in the induction of immunity by recognition, capture, process, and presentation of antigens from infectious microbes. Streptococcus gordonii is able to cause life-threatening systemic diseases such as infective endocarditis. Serine-rich repeat (SRR) glycoproteins of S. gordonii are sialic acid-binding adhesins mediating the bacterial adherence to the host and the development of infective endocarditis. Thus, the SRR adhesins are potentially involved in the bacterial adherence to DCs and the maturation and activation of DCs required for the induction of immunity to S. gordonii. Here, we investigated the phenotypic and functional changes of human monocyte-derived DCs treated with wild-type S. gordonii or the SRR adhesin-deficient mutant. The mutant poorly bound to DCs and only weakly increased the expression of CD83, CD86, MHC class II, and PD-L1 on DCs compared with the wild-type. In addition, the mutant induced lower levels of TNF-α, IL-6, and IL-12 than the wild-type in DCs. When DCs sensitized with the mutant were co-cultured with autologous T cells, they induced weaker proliferation and activation of T cells than DCs stimulated with the wild-type. Blockade of SRR adhesin with 3’-sialyllactose markedly reduced S. gordonii binding and internalization, causing attenuation of the bacterial immunostimulatory potency in DC maturation. Collectively, our results suggest that SRR adhesins of S. gordonii are important for maturation and activation of DCs.